2020
DOI: 10.1007/s00343-019-9216-4
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth, and mortality rate of the yellow goosefish Lophius litulon (Jordan, 1902) in the Yellow Sea

Abstract: With the decline in the most fi sheries resources in the Yellow Sea, the yellow goosefi sh Lophius litulon has increased in commercial and ecological importance in recent years. We studied the length distribution, length-weight relationship, age composition, growth pattern, mortality, and exploitation rates of the yellow goosefi sh in the Yellow Sea. Total length (TL) of females and males ranged from 173 to 582 mm and 178 to 500 mm, respectively. The length-weight relationships were also estimated for females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…The evaluation results obtained through multiple methods ensure the accuracy of the assessment and determine the M value of X. argentea in the lower reaches of the Tangwang River was 0.346 yr −1 . Li & Chen (2009) suggested that an exploitation rate of 0.5 is considered most suitable for fish populations, with fishing mortality being equivalent to natural mortality ( Sun et al, 2021 ). In this study, the E value of X. argentea was 0.574, which was higher than 0.5, similar to L. waleckii in the lower reaches of the Tangwang River ( Lu et al, 2019 ) and S. argentatus in the lower reaches of the Songhua River ( Lu et al, 2023 ), indicating that X. argentea has been overexploitated under the current fishing intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation results obtained through multiple methods ensure the accuracy of the assessment and determine the M value of X. argentea in the lower reaches of the Tangwang River was 0.346 yr −1 . Li & Chen (2009) suggested that an exploitation rate of 0.5 is considered most suitable for fish populations, with fishing mortality being equivalent to natural mortality ( Sun et al, 2021 ). In this study, the E value of X. argentea was 0.574, which was higher than 0.5, similar to L. waleckii in the lower reaches of the Tangwang River ( Lu et al, 2019 ) and S. argentatus in the lower reaches of the Songhua River ( Lu et al, 2023 ), indicating that X. argentea has been overexploitated under the current fishing intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, populations of the same species residing in different geographical locations or experiencing varying growth environments may exhibit distinct interpopulation variations [42]. The slope b of length-weight relationship, growth coefficient K, growth characteristic index (ϕ) are the key parameters to evaluate the growth potential of fish population [43,44]. According to Onikura and Nakajima [45], the b value reflects the growth pattern of fish, and when b is close to "3", it is isometric growth, otherwise, it is allometric growth.…”
Section: Discussionmentioning
confidence: 99%
“…The exploitation rate (E) of fish is an important parameter in fishery management [44]. The reasonable exploitation intensity of fish should be less than 0.5, less than this intensity is mild development, and higher than this intensity is overexploitation, which will have a negative impact on the sustainability of fish stocks [53].…”
Section: Discussionmentioning
confidence: 99%
“…The study of population characteristics such as age, growth, and mortality in fish is fundamental to fisheries resource assessment and management, as these characteristics are influenced by genetic factors and the natural environment [ 7 , 16 , 17 ]. Prolonged fishing pressures and environmental changes have resulted in variations in species diversity, community structure, and food webs in aquatic ecosystems and have influenced the dynamics of various hydrobios [ 18 20 ]. The potential changes in phenotypic characteristics and biological indicators of the G. huanghensis population under long-term survival pressure warrant our attention.…”
Section: Introductionmentioning
confidence: 99%